Association of Schistosoma haematobium infection morbidity and severity on co-infections in pre-school age children living in a rural endemic area in Zimbabwe - Tariro L. Mduluza-Jokonya; Thajasvarie Naicker; Luxwell Jokonya; Herald Midzi; Arthur Vengesai; Maritha Kasambala; Emilia Choto; Simbarashe Rusakaniko; Elopy Sibanda; Francisca Mutapi; Takafira Mduluza (BMC, 2020)
Abstract Background Individuals living in Schistosoma haematobium endemic areas are often at risk of having other communicable diseases simultaneously. This usually creates diagnostic difficulties leading to misdiagnosis and overlooking of schistosomiasis infection. In this study we investigated the prevalence and severity of coinfections in pre-school age children and further investigated associations between S. haematobium prevalence and under 5 mortality. Methods A community based cross-sectional survey was conducted in Shamva District, Zimbabwe. Using random selection, 465 preschool age children (1-5 years of age) were enrolled through clinical examination by two independent clinicians for the following top morbidity causing conditions: respiratory tract infections, dermatophytosis, malaria and fever of unknown origin. The conditions and their severe sequels were diagnosed as per approved WHO standards. S. haematobium infection was diagnosed by urine filtration and the children were screened for conditions common in the study area which included HIV, tuberculosis, malnutrition and typhoid. Data was analysed using univariate and multinomial regression analysis and relative risk (RR) calculated. Results Prevalence of S. haematobium was 35% (145). The clinical conditions assessed had the following prevalence in the study population: upper respiratory tract infection 40% (229), fever of unknown origin 45% (189), dermatophytosis 18% and malaria 18% (75). The odds of co-infections observed with S. haematobium infection were: upper respiratory tract infection aOR = 1.22 (95% CI 0.80 to 1.87), dermatophytosis aOR = 4.79 (95% CI 2.78 to 8.25), fever of unknown origin aOR = 10.63 (95% CI 6.48-17.45) and malaria aOR = 0.91 (95% CI 0.51 to1.58). Effect of schistosomiasis coinfection on disease progression based on the odds of the diseases progressing to severe sequalae were: Severe pneumonia aOR = 8.41 (95% CI 3.09-22.93), p < 0.0001, complicated malaria aOR = 7.09 (95% CI 1.51-33.39), p = 0.02, severe dermatophytosis aOR = 20.3 (95% CI 4.78-83.20):p = 0.03, and fever of unknown origin aOR = 1.62 (95%CI 1.56-4.73), p = 0.02. Conclusion This study revealed an association between schistosomiasis and the comorbidity conditions of URTI, dermatophytosis, malaria and FUO in PSAC living in a schistosomiasis endemic area. A possible detrimental effect where coinfection led to severe sequels of the comorbidity conditions was demonstrated. Appropriate clinical diagnostic methods are required to identify associated infectious diseases and initiate early treatment of schistosomiasis and co-infections in PSAC.